About the Disciplinary Status of Education (Praxis Educativa, 2023)
After theoretical debate around the inter or transdisciplinary character related to production of knowledge at the contemporary university; Education was again being moved back to the epistemological tribunal. No longer by its condition as a discipline, but due to that the trait of discipline itself faced the institutional demise.With that dilemma, a former question returned in educational field, namely: how Education might be comprehended as scientific discipline? That question turns out to be essential to ponder the epistemic role of educational research. Oriented to that, the notion of academic discipline is examined, exploring their conceptual requirements and limits. Accordingly, the Wilfred Carr`s theoretical proposal of educative practice is revisited, and connected with two fundamental epistemic dimensions for understanding the meaning of discipline of knowledge: the disciplinary language and object. Finally, it is concluded that the concept of educational practice is crucial to defend the disciplinary status of education.
Keywords: education; disciplines; educational theory; educative practice; philosophy of education